Phase Diagram and Waterlike Anomalies in Core-Softened Shoulder-Dumbbell Complex Fluids - Netz, Paulo A.; Gonzatti, Guilherme K.; Barbosa, Marcia C.; Paukowski, Juliana Z.; Gavazzoni, Cristina; Oliveira, Alan Barros de (IntechOpen, 2011)
None